Bendable large-mode-area fiber with a non-circular core - Ji, Junhua (2020)
We investigate mode-area-scaling and bending performances of a Yb-doped large-mode-area fiber with an elongated non-circular core. Such fiber can be bent in the plane of its short axis to suppress bending effects, such as mode area reduction and mode profile distortion. Meanwhile, the other orthogonal axis can be stretched for mode area scaling. Calculations show that for fibers with the same mode area, the higher the aspect ratio between the long axis and short axis, the less sensitive the fiber will be to bending effects. However, mode area scaling is limited by the increased beat length (BL) between the fundamental mode (FM) and the second-order mode, leading to mode degeneracy at higher aspect ratios. Within the 100 mm BL, the FM area is scalable to 3000  μm2 in a bent fiber. To facilitate FM operation, we study mode-selective gain through confined doping. Thanks to the small bending distortions, the confined-doping approach works well in the bent large-mode-area fiber. In addition, the advantage of tandem pumping is also discussed in terms of preferential modal gain. A non-circular core fiber with a 41 μm short axis and 120 μm long axis was fabricated in-house. We evaluated the fiber in a linear laser cavity pumped by a 975 nm laser diode. The maximum output power obtained was 191 W, with slope efficiency of approximately 67% with respect to launched pump power. The output signal has good beam qualities with M2 of ∼1.5 and ∼3.1, respectively, along the short and long axis.